Teologi Katolik Menerangi Pemahaman Masyarakat Batak Toba Tentang Roh - Olly Sardiman Situmorang; Megawati Naibaho; Antonius P. Sipahutar (Journal New Light, 2024)
The writing of this thesis begins with the emergence of the author’s awarenes of the importance of understanding spirits of the Toba Batak culture in harmony with Catholic Theology. The meaning of spirit in Toba Batak culture is often understood both among the Toba Batak people and from other tribes, as a custom of idol worship. Chatolic Theology confirms that the spirit is a divine power that work in every creation, transport in all living things and is active in humans, specifically the Holy Spirit that is bestowed by God in every human being. The existence of the Holy Spirit in human being is a gift fom God himself to support human being to life. The religion and cultural customs are not two things that go in contradictory directions, but they are two features that strengthen each other. The culture is inherent in human existence from birt, and the religion is a way for human being to identify the faith in Jesus Christ himseft. A human being who is cultured and trough the help of the Holy Spirit will be able to experience oneness with God. Thus, the Religion and culture are two characteristics that lead human beings to the equal goal, namely human self-improvement.